The mode II interlaminar fracture testing of glass fibre reinforces thermoset composites - Ismail, Yob Saed; Abu Hassan, Shukur; Abd. Kader, Abd. Saman; Chong, Chin Lee (Faculty of Mechanical Engineering, UTM, 2004)
This paper presents the result of setting up the end notched flexure (ENF) testing to determine the Mode-II interlaminar fracture toughness on various forms of E-glass fibre/thermoset based composites. The materials tested are unidirectional, woven roving and chopped strands mat with polyester and epoxy resins and were manufactured by hand lay up technique. The preparation process, testing procedure and data reduction scheme of the ENF specimen are described in details. To verify the result of this work, the Mode-II critical strain energy release rate, GIIc, for the tested materials is compared to those found in other publications. This study successfully demonstrates the simplicity and effectiveness of the ENF specimen in evaluating the Mode-II fracture toughness of E-glass fibre/thermoset based composites.